ANALISIS KECELAKAAN LALU LINTAS DENGAN METODE ANGKA KECELAKAAN BERBASIS JARAK DAN BERBASIS PANJANG PERJALANAN KENDARAAN TOTAL (STUDI KASUS : JALAN SILIWANGI – WALISONGO, SEMARANG KM SMG 7+200 – KM SMG 8+100) - Anton Gazali Thoib; Nico Bakista Satriawan; Bambang Riyanto; Kami Hari Basuki (Jurnal Karya Teknik Sipil, 2014)
Siliwangi – Walisongo road is a primary arterial road which connects the city of Semarang and Kendal. Siliwangi – Walisongo road. Siliwangi – Walisongo road is a track of “Pantura” which always crowded with traffic all the time. The density of traffic flow on the Siliwangi  – Walisongo road pose a high risk of accident on the road. Accident data from November 2012 till Oktober 2013 which obtained from Polda Jateng reports indicate that on the Siliwangi  – Walisongo road KM SMG 7+200 – KM SMG 8+100 there were 16 cases with 4 victims died and 13 were lightly wounded casualties. Based on the description above, it is necessary to analyze the accident on the accident prone area. This study begins by doing  library research and survey advances, then procced with collecting the secondary data and primary data. Primary data in the form of survey complatness infrastructure and road situations. Secondary data in the form of accidents on Siliwangi – Walisongo road KM SMG 7+200 – KM SMG 8+100, cross sectional and longitudinal images path, the data volume of the vehicle and the map of Siliwangi – Walisongo road. Method of analysis consisted of analysis of the relationship between variables, accident rate based on  distance and accident rate based on vehicle miles. The result showed, the volume of vehicles has a close relationship with a number of accidents that occur, the most influential factor of accident is the driver, and the driver’s lack of anticipation is the  largest  factor  of accidents. Accident rate based on distance resulted thah accident rate on segment 6, segment 13 and segment 16 exceeds the upper limit of the accident rate, while the accident rate based on vehicle miles, each segment doesn’t exceed the upper limit of the accident rate.